Leaf litter breakdown along an elevational gradient in Australian alpine streams. Issue 10 (18th October 2022) - Werry, Lloyd P.; Bundschuh, Mirco; Mitrovic, Simon M.; Lim, Richard P.; Kefford, Ben J.
Abstract: The breakdown of allochthonous organic matter, is a central step in nutrient cycling in stream ecosystems. There is concern that increased temperatures from climate change will alter the breakdown rate of organic matter, with important consequences for the ecosystem functioning of alpine streams. This study investigated the rate of leaf litter breakdown and how temperature and other factors such as microbial and invertebrate activities influenced this over elevational and temporal gradients. Dried leaves of Snow Gum ( Eucalyptus pauciflora ) and cotton strips were deployed in coarse (6 mm), and fine (50 μm) mesh size bags along an 820 m elevation gradient. Loss of mass in leaf litter and cotton tensile strength per day ( k per day), fungal biomass measured as ergosterol concentration, invertebrate colonization of leaf litter, and benthic organic matter (mass and composition) were determined. Both microbial and macroinvertebrate activities were equally important in leaf litter breakdown with the abundance of shredder invertebrate taxa. The overall leaf litter breakdown rate and loss of tensile strength in cotton strips (both k per day) were greater during warmer deployment periods and at lower elevations, with significant positive relationships between mean water temperature and leaf breakdown and loss of tensile strength rate, but no differences between sites, after accounting for the effects of temperature. Despite considerably lower amounts of benthic organic matter in streams above the tree line relative to those below, shredders were present in coarse mesh bags at all sites. Ergosterol concentration was greater on leaves in coarse mesh bags than in fine mesh bags, implying differences in the microbial communities. The importance of water temperatures on the rate of leaf litter breakdown suggests the potential effects of climate change‐induced temperature increases on ecological processes in such streams. Abstract : We aimed at understanding how spatial and temporal water temperatures influenced AOM breakdown in alpine streams. Microbial and macroinvertebrate activities were monitored and showed to be elevated at lower elevations and during warmer periods. Climate change induced warming will therefore potentially change alpine stream ecosystem, standing biomass and promote increased nutrient cycling through AOM breakdown.